Genetic diversity of the coat protein of Olive mild mosaic virus (OMMV) and Tobacco necrosis virus D (TNV-D) isolates and its structural implications. - Carla M R Varanda (Public Library of Science (PLoS), 2014)
The genetic variability among 13 isolates of Olive mild mosaic virus (OMMV) and of 11 isolates of Tobacco necrosis virus D (TNV-D) recovered from Olea europaea L. samples from various sites in Portugal, was assessed through the analysis of the coat protein (CP) gene sequences. This gene was amplified through reverse transcriptase polymerase chain reaction (RT-PCR), cloned, and 5 clone sequences of each virus isolate, were analysed and compared, including sequences from OMMV and TNV-D isolates originally recovered from different hosts and countries and available in the GenBank, totalling 131 sequences. The encoded CP sequences consisted of 269 amino acids (aa) in OMMV and 268 in TNV-D. Comparison of the CP genomic and amino acid sequences of the isolates showed a very low variability among OMMV isolates, 0.005 and 0.007, respectively, as well as among TNV-D isolates, 0.006 and 0.008. The maximum nucleotide distances of OMMV and TNV-D sequences within isolates were also low, 0.013 and 0.031, respectively, and close to that found between isolates, 0.018 and 0.034, respectively. In some cases, less variability was found in clone sequences between isolates than in clone sequences within isolates, as also shown through phylogenetic analysis. CP aa sequence identities among OMMV and TNV-D isolates ranged from 84.3% to 85.8%. Comparison between the CP genomic sequences of the two viruses, showed a relatively low variability, 0.199, and a maximum nucleotide distance between isolates of 0.411. Analysis of comparative models of OMMV and TNV-D CPs, showed that naturally occurring substitutions in their respective sequences do not seem to cause significant alterations in the virion structure. This is consistent with a high selective pressure to preserve the structure of viral capsid proteins.